Social Entrepreneurship is Being Utilized to Address The Issue of Food Waste in The Region of West Java - Hastuti, Ika Sri; Sawitri, Anggi; Poerwantika, Tine Ratna (Journal of Indonesian Social Sciences and Humanities, 2022)
Indonesia, the greatest waste producer in Southeast Asia, is grappling with a significant issue of food waste, which makes up 41.07% of the nation’s overall waste. Waste4Change, a social enterprise specializing in sustainable trash management, is collaborating with the Bekasi administration to address the issue resulting from insufficient public awareness. The study elucidates Waste4Change’s role in attaining the 12th Sustainable Development Goal (SDG) in West Java. This is accomplished through the utilization of descriptive analysis methods and data collection approaches such as interviews and literature studies. Waste4Change employs norm life cycle theory and a global governance strategy to transform the way society manages food waste. Studies indicate that Waste4Change has adopted a comprehensive strategy for waste management by utilizing campaigns, teaching, and collaboration. However, limitations in infrastructure, technology, and resources hinder individuals from acquiring further knowledge on the subject of food waste management. Further assessments are required to determine the long-term efficacy of Waste4Change in attaining sustainable development objectives in West Java.